PENGARUH CORPORATE ENVIRONMENTAL DISCLOSURE DAN EARNINGS MANAGEMENT DENGAN THE LARGEST SHAREHOLDERS SEBAGAI MODERASI - Ummu Huaida, (2023)
This research is quantitative research to empirically prove the effect of corporate environmental disclosure which consists of environmental policy, environmental pollution, environmental energy, and environmental financial on earnings management with the largest shareholders acting as a moderating variable as well as profitability, leverage, firm size, and the size of a public accounting firm (KAP) as a control variable. Earnings management is measured using the Cohen and Zarowin (2010) model, which is the sum of abnormal operating cash flows and abnormal discretionary expenses as model one and the sum of abnormal production costs and abnormal discretionary expenses as model 2. The study uses secondary data, namely non-financial companies registered on Indonesia Stock Exchange for the 2019-2021 period. The total sample size is 198 samples using the panel data regression analysis method with the help of the STATA 14 application. The results of the study state that environmental policy, environmental pollution, environmental energy, and environmental finance have no significant effect on earnings management either in model 1 or model 2.